Computer Science &Amp; Information Technology ( CS &Amp; IT ) 2014
DOI: 10.5121/csit.2014.4809
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Client Side User Profiling for Improving Relevancy of Search Results

Abstract: The Web is being a pool of knowledge, where any user visits hundreds of pages for various purposes but keeping track of its relevance for him is a tedious job. An average browser just provides you by the details of your browsing history but has no way to determine what importance the page holds for the user. In this paper we propose a method which aims to generate user profiles automatically depending on the various web pages a user browses over a period of time and the user's interaction with them. This autom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Methods on which the entire implicit feedback model relies are copy to clipboard, mouse activity and scroll activity. From these, Clipboard data and mouse activity can be captured using a few lines of JavaScript code included in the browsers [31,32]. Research reported based on smartphone sensor data, requires data collector method with respect to the context the data is required.…”
Section: Data Collectorsmentioning
confidence: 99%
“…Methods on which the entire implicit feedback model relies are copy to clipboard, mouse activity and scroll activity. From these, Clipboard data and mouse activity can be captured using a few lines of JavaScript code included in the browsers [31,32]. Research reported based on smartphone sensor data, requires data collector method with respect to the context the data is required.…”
Section: Data Collectorsmentioning
confidence: 99%
“…Methods on which the entire implicit feedback model relies are copy to clipboard, mouse activity and scroll activity. From these, Clipboard data and mouse activity can be captured using a few lines of JavaScript code included in the browsers [21], [22]. Research reported based on smartphone sensor data, requires data collector method with respect to the context the data is required.…”
Section: Data Collectorsmentioning
confidence: 99%